Influence of electrolytes on the clouding and thermodynamic nature of non-ionic surfactant in the presence of an antibiotic drug. (3rd September 2021) - Khan, Muhammad Akhlaqur Rahman; Amin, Md. Ruhul; Patoary, Mohammad-Omar-Faruk; Rub, Malik Abdul; Hoque, Md. Anamul; Khan, Mohammed Abdullah; Kumar, Dileep; Asiri, Abdullah M.; Khan, Farah; Alfaifi, Sulaiman Y.M.
ABSTRACT: The cloud point (CP) of a mixture of Tween 80 (Tw 80) and neomycin sulphate (NS) was measured in an aqueous medium containing electrolyte (NaCl, NaNO3, and Na2 SO4 ). The CP of Tw 80 decreased when Tw 80 concentration increased. For various concentrations of Tw 80 (1.53 × 10 –2, 3.05 × 10 –2, and 6.11 × 10 –2  mol.kg -1 ), CP values of the solution decreased with increasing additions of NS. CP values of NS+Tw 80 mixtures also decreased upon the addition of salts, following the trend: CPNa 2 SO4 > CPNaNO3 > CPNaCl . Thermodynamic variables including standard-free energy (∆ G 0 c), standard enthalpy (∆ H 0 c), and standard entropy (∆ S 0 c) of clouding as well as thermodynamic properties of transfer during phase transition were also determined. A linear relationship between enthalpy change (∆ H 0 c) and entropy change (∆ S 0 c) with an R 2 value of 0.9997–1.00 was obtained for the Tw 80+ NS mixture in aqueous electrolyte media.